2017
DOI: 10.1016/j.ijheh.2017.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Ocular symptoms and tear film break up time (BUT) among junior high school students in Penang, Malaysia – Associations with fungal DNA in school dust

Abstract: a b s t r a c tBackground: There are few studies on ocular effects of indoor mould exposure in schools, especially in the tropics Objective: To study associations between eye symptoms and tear film break up time (BUT) in students and demographic data and fungal DNA in schools. Methods: A school environment study was performed among randomly selected students in eight randomly selected secondary schools in Penang, Malaysia. Information on eye symptoms and demographic data was collected by a standardised questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
1
4
0
1
Order By: Relevance
“…The role of biomarkers in airways is complex and specific, which is helpful in evaluating the aetiology, characterisation of phenotyping, and treatment of allergy and lung inflammation [ 37 ]. In this study, the FeNO levels were significantly higher among asthmatic school children, which are similar with the studies conducted in China [ 38 ], Terengganu, Malaysia [ 39 ], and Penang, Malaysia [ 40 ]. The result showed that there was inflammation in the airways and the average value was above the threshold of 50 ppb, which could reflect a high degree of inflammation.…”
Section: Discussionsupporting
confidence: 90%
“…The role of biomarkers in airways is complex and specific, which is helpful in evaluating the aetiology, characterisation of phenotyping, and treatment of allergy and lung inflammation [ 37 ]. In this study, the FeNO levels were significantly higher among asthmatic school children, which are similar with the studies conducted in China [ 38 ], Terengganu, Malaysia [ 39 ], and Penang, Malaysia [ 40 ]. The result showed that there was inflammation in the airways and the average value was above the threshold of 50 ppb, which could reflect a high degree of inflammation.…”
Section: Discussionsupporting
confidence: 90%
“…In their paper they found out the sta ng of staff including EHPs in leadership positions at the districts of Bunyangabo and Ntoronko (Uganda) required ling in bid to improve decision making for better service delivery [9]. Furthermore, the need to have environmental health professionals is underlined by Norback et al (2017) citing that environmental health is key and crucial to the concept of sustainable development [10].Our survey results revealed that there are few EHPs employed substantively in leadership and managerial positions like Assistant district health o cers, commissioners. Furthermore, it should also be noted that in Ugandan setting such leadership positions are few for example a whole district requires only one o cer or three in such leadership positions and this could be the explanation for the observed results.…”
Section: Discussionmentioning
confidence: 99%
“…Die Tränenfilmabrisszeit, die beispielsweise in einer Studie von Norbäck et al (2017) 696 eine Assoziation mit Pilz-DNA im Staub von Klassenräumen zeigt, eignet sich aufgrund vielfältiger anderer Einflussfaktoren nicht für die individuelle medizinische Diagnostik zur Objektivierung von Innenraumschimmel-assoziierten Augenbeschwerden.…”
Section: Diagnostikunclassified